Noise in Brazilian Clinical Anamnesis: An Empirical Study - Carvalho, Leandro A.; Oliveira, Thiago Q.; Sousa, Flávio R. C.; F. Filho, João B. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248362, 2026)
Research Context: The lack of representative data can limit the development of robust clinical Natural Language Processing (NLP) models, as models trained on idealized data can perform poorly on noisy real-world Electronic Health Records (EHRs). Scientific and/or Practical Problem: A performance gap exists when these NLP models are deployed on noisy, real-world clinical text. This issue can be found in less-resourced languages, such as Brazilian Portuguese, where the scarcity of data can limit the development of effective clinical information systems. Proposed Solution and/or Analysis: This study addresses this challenge by presenting a systematic approach to identify and quantify textual noise patterns found in Brazilian Portuguese clinical narratives. Related IS Theory: Based in Task-Technology Fit (TTF) Theory, this study investigates the misalignment between the task of reliable information extraction from noisy EHRs and the technology of NLP models, which can presuppose clean data. Research Method: A multi-stage methodology was employed to identify textual noise. Starting with a classification stage to flag candidate tokens likely representing typos and abbreviations, followed by a lexicon-based validation executed to refine this selection, ensuring that only authentic noise instances were selected. Summary of Results: The analysis of a dataset of clinical anamneses revealed not only a high incidence of textual noise, but also a consistent recurrence of specific noisy tokens across the dataset, demonstrating the widespread nature of data quality issues in this domain. Contributions and Impact to IS area: A taxonomy of textual noise, complemented by two JSON files that structurally map the noisy tokens, establishing an empirical benchmark for Brazilian Portuguese clinical text and formalizing the data quality challenges that must be overcome for successful NLP implementation.